Case Report: One alternative surgical treatment for retrograde peri-implantitis - Matthew J Hoffman; Demetria D Hale; Kenneth L Hale (Frontiers Media S.A., 2022)
BackgroundRetrograde peri-implantitis is an infection at the apex of an implant, leading to progressive bone loss. We present a surgical technique that is an alternative to implant removal or "implantoplasty."CaseA 47-year-old patient developed retrograde peri-implantitis 18 months after implant placement. As the infection was localized to the apex of the implant, an apicoectomy was performed on the implant. Post-operative serial periapical radiographs showed reparative tissue within 4 months, and a follow-up radiograph showed complete bone restoration 2 years later.Practical ImplicationsThe findings of this case suggest a viable alternative to condemnation and removal of an implant with a periapical infection. It may be viable to resect the contaminated portion of the implant, graft the defect, and gain long-term retention and service of the implant.